2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944067
|View full text |Cite
|
Sign up to set email alerts
|

Relation between heart beat fluctuations and cyclic alternating pattern during sleep in insomnia patients

Abstract: Insomnia is a condition that affects the nervous and muscular system. Thirty percent of the population between 18 and 60 years suffers from insomnia. The effects of this disorder involve problems such as poor school or job performance and traffic accidents. In addition, patients with insomnia present changes in the cardiac function during sleep. Furthermore, the structure of electroencephalographic A-phases, which builds up the Cyclic Alternating Pattern during sleep, is related to the insomnia events. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It has been applied to the evaluation of posture [17], exercise [18] and sleep stage classification [19], and classification of asthma [20] and COPD [16,21,22].…”
Section: Detrended Fluctuation Analysis (Dfa)mentioning
confidence: 99%
“…It has been applied to the evaluation of posture [17], exercise [18] and sleep stage classification [19], and classification of asthma [20] and COPD [16,21,22].…”
Section: Detrended Fluctuation Analysis (Dfa)mentioning
confidence: 99%
“…Among the most common sleep complaints in the elderly are insomnia (population frequency ranging from 23 to 34%), and difficulty feeling rested upon waking (7–15%) (1) . Experimental studies in both animals and humans have demonstrated that disruptions in sleep patterns exert considerable effects on brain health (2) .…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent insomnia and SDB could be associated with distinct alterations in sleep physiology. Sleep microstructure [42][43][44][45][46], arousal thresholds [42,47], and sleep fragmentation [10] are aspects of sleep physiology affected in both SDB and insomnia, any of which could mediate a relationship between SDB with comorbid insomnia and the risk of cognitive impairment. Sleep fragmentation has been prospectively associated with an increased risk of incident Alzheimer's disease at 6-year follow-up [48].…”
Section: Discussionmentioning
confidence: 99%